Mentoring for the Competition: Implementation of Seven Dimensions of Resilient Elderly in Elderly Activity Groups in Lamper Krajan Area - Pustika Dewi, Restu Ayu Eka; Arumsari, Wahyuni; Siti Marchamah, Dwi Nur (Edumedia Solution, 2025)
Aging is a natural process experienced by all living beings, including humans. As people age, they often experience a decline in cognitive and physiological functions. This decline increases the risk of degenerative diseases such as hypertension, diabetes, and cancer, which can significantly impact the quality of life and productivity of the elderly. The concept of the Seven Dimensions of Resilient Elderly serves as a framework to enhance the quality of life and promote more productive living for the elderly. By implementing the Seven Dimensions of Resilient Elderly, the quality of life for older adults can be significantly enhanced, enabling them to lead more productive lives. The objective of this community service initiative is to mentor the volunteers of the Elderly Family Development Group, known as